Ground displacement of the 6 July 2019 Ridgecrest earthquake from the GNSS permanent stations - Lau, Nguyen Ngoc; Trinh, Phan Trong; Phong, Tran Van; Pham, Binh Thai (Vietnam Journal of Earth Sciences, 2019)
The Eastern California earthquake (also known as the Ridgecrest earthquake) occurred at 03:19:53 (UTC) on the 6th of July, with a moment magnitude of 7.1. Over the region, there is an accurate network of GNSS permanent stations. Precise determination of displacements of these stations will provide important information to better understand the structure and scope of the earthquake, contributing to faster and more accurate earthquake prediction. In this paper, we used precise point positioning with ambiguity resolution to determine the co-seismic displacements of 25 GNSS stations around the epicenter for the day of the earthquake. The processing results show that the affected area being more than 100 km centered around the earthquake epicenter with the largest value being approximately 0.6 m.